Комунікативний аспект кримінально-правового нормування в Україні - Лантінов, Я. О.; Lantinov, Ya. O.; ORCID: https://orcid.org/0000-0002-1858-6842 (Форум Права. – 2023. – № 1 (74). – С. 98-105, 2023)
Надано характеристику одному з аспектів явища кримінально правового нормування, а саме комунікативного, як того з сутнісних, що зазвичай оминається у спеціальних дослідженнях. З'ясовано основні положення теорій комунікації та зіставлено їх з вченням про кримінально-правове нормування. Запропоновано в якості характеристики комунікативного аспекта кримінально-правового регулювання пояснення, що воно виступає "ядром" сучасного кримінально-правового регулювання, останнє ж належить до типу "command and control", та водночас, кримінально-правове регулювання є формою "управління людиною людини", яке є комунікативною діяльністю по суті.

The production of criminal norms is an integral part of criminal regulation – this is one of the fundamental principles of Ukrainian Criminal Law theory. However, Ukrainian scholars do not give enough attention to the production of criminal norms as a communicative process. The purpose of this article is to characterize the communicative aspect of the production of criminal norms, which is often overlooked in existing studies. The mandatory criteria of "falsifiability," "verifiability," "productivity," and "logic" are recognized as peripheral in the research methodology. The main research method used was the formal dogmatic method, which involves deductive, inductive, and traductive reasoning to clarify theoretical constructs by analyzing, comparing, and establishing compliance with the rules of attribution to concepts and terms. In addition, the system method was applied in an experiment with Internet search thoughts. The results of the study include a summary of the history of the study of communication and the development of both a universal view of communication (communication as a category) and diversified explanations (by fields of knowledge and practical activity) within this framework. Communication is presented as a phenomenon (a mechanism) that enables the division of labor, the separation of management, the formation of a complex society, and the formation of the state and law. Although any activity is influenced by communication and has a communicative aspect, some activities are purely communicative, such as "management" in both its direct form, i.e., in management, and indirect form, i.e., in regulation. Conclusions. The article concludes that the communicative aspect of the production of criminal norms is the "core" of modern criminal law regulation in Ukraine, which belongs to the "command and control" type, and at the same time, criminal law regulation is a form of "management," which is essentially a communicative activity.

Дана характеристика одному из аспектов явления уголовно-правового нормирования, а именно коммуникативного, как того из сущностных, что обычно обходится в специальных исследованиях. Выяснены основные положения теорий коммуникации и сопоставлено их с учением об уголовно-правовом нормировании.
Communicative aspects of criminal law regulation in Ukraine
Лантінов, Я. О. Комунікативний аспект кримінально-правового нормування в Україні [Електронний ресурс] / Я. О. Лантінов // Форум Права. – 2023. – № 1 (74). – С. 98-105. - Режим доступу:http://forumprava.pp.ua/files/098-105-2023-1-FP-Lantinov_10.pdf.
Лантінов, Я. О. (2023). Комунікативний аспект кримінальноправового нормування в Україні. Форум Права, 74(1), 98–105. http://doi.org/10.5281/zenodo.7319906.
Lantinov, Y. A. (2023). Komunikatyvnyy aspekt kryminalno-pravovoho normuvannya v Ukrayini [Communicative Aspects of Criminal Law in Ukraine]. Forum Prava, 74(1), 98–105. http://doi.org/10.5281/zenodo.7319906.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінально-правове нормування; criminal law regulation; уголовно-правовое нормирование; комунікативний аспект; communicative aspect; коммуникативный аспект; комунікація; communication; коммуникация; поділ праці; division of labor; разделение труда; управління; management; управление